Clinical prediction rules for abusive head trauma: a systematic review. Issue 8 (5th April 2018) - Pfeiffer, Helena; Crowe, Louise; Kemp, Alison Mary; Cowley, Laura Elizabeth; Smith, Anne S; Babl, Franz E
Abstract : Objective: Misdiagnosis of abusive head trauma (AHT) has serious consequences for children and families. This systematic review identifies and compares clinical prediction rules (CPredRs) assisting clinicians in assessing suspected AHT. Design: We searched MEDLINE, Embase, PubMed and Cochrane databases (January 1996 to August 2016). Externally validated CPredRs focusing on the detection of AHT in the clinical setting were included. Results: Of 110 potential articles identified, three studies met the inclusion criteria: the Pediatric Brain Injury Research Network (PediBIRN) 4-Variable AHT CPredR, the Predicting Abusive Head Trauma (PredAHT) tool and the Pittsburgh Infant Brain Injury Score (PIBIS). The CPredRs were designed for different populations and purposes: PediBIRN: intensive care unit admissions (<3 years) with head injury, to inform early decisions to launch or forego an evaluation for abuse (sensitivity 0.96); PredAHT: hospital admissions (<3 years) with intracranial injury, to assist clinicians in discussions with child abuse specialists (sensitivity 0.72); and PIBIS: well-appearing children (<1 year) in the emergency department with no history of trauma, temperature <38.3°C, and ≥1 symptom associated with high risk of AHT, to determine the need for a head CT scan (sensitivity 0.93). There was little overlap between the predictive variables. Conclusion: Three CPredRs for AHT were relevant at different stages in the diagnostic process. None of the CPredRs aimed to diagnose AHT but to act as aids/prompts to clinicians to seek further clinical, social or forensic information. None were widely validated in multiple settings. To assess safety and effectiveness in clinical practice, impact analyses are required and recommended.